Techno-economic Analysis of Boric Acid Production from Colemanite Mineral and Sulfuric Acid. (3rd April 2022) - Gönen, Mehmet; Rodene, Dylan D.; Panda, Sandeep; Akcil, Ata
ABSTRACT: In the present study, a sustainable production of boric acid from colemanite mineral and sulfuric acid was investigated, considering waste treatment and colemanite mineral processing costs. The purchasing price of sulfuric acid and the selling price of boric acid obtained from the market were used as $50/t and $900/t, respectively, to perform the simulation via professional SuperPro designer (v.9.0). The effect of the colemanite mineral price was investigated between $50 and $250/t for a 100 kt.y −1 plant capacity. The effect of a waste treatment cost was investigated by applying values between $10 and $50/ton for a 100 kt.y −1 plant capacity. The annual waste treatment cost was calculated using the value of $50/ton and was found to be $9.3 M, which contributes to the operating cost by 13.4%. The most significant components that influenced the boric acid production costs were determined to be the facility-dependence (41.9%) and cost of the raw materials (30.3%). The fixed capital investment and annual operating costs of the boric acid plant are calculated as $170.7 M and $70.1 M/y, respectively, for a 100 kt.y −1 capacity. The unit production cost of boric acid having an impurity of <100 ppm was calculated as $0.70 kg −1 . Therefore, a payback time of 6.3 years was estimated from the economic analysis of a commercial boric acid production process including environmental impacts.